2013
DOI: 10.1590/s1413-78522013000300009
|View full text |Cite
|
Sign up to set email alerts
|

Polimorfismo do gene da eca e da α-actinina 3 na escoliose idiopática do adolescente

Abstract: OBJECTIVE: The I/D polymorphism of angiotensin-converting enzyme (ACE) and R577X of the α-actinin-3 (ACTN3) is related to changes in skeletal muscle function. The aim of this study was to evaluate the distribution of these polymorphisms in a family with multiple members with adolescent idiopathic scoliosis (AIS). METHODS: Evaluated 25 subjects from a family with multiple members with AIS, by collecting 10mL of blood for DNA isolation. The genotyping of the I/D polymorphism of the ACE gene and the R577X of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
1
3
0
1
Order By: Relevance
“…Our analysis of genotypic frequencies showed the DD genotype and D allele were highest in patients with AIS, in agreement with results reported by Wajchenberg et al (2013) in a family with multiple members with AIS. We also observed that the incidence of the II genotype in healthy individuals was twice that in patients with AIS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our analysis of genotypic frequencies showed the DD genotype and D allele were highest in patients with AIS, in agreement with results reported by Wajchenberg et al (2013) in a family with multiple members with AIS. We also observed that the incidence of the II genotype in healthy individuals was twice that in patients with AIS.…”
Section: Discussionsupporting
confidence: 92%
“…The human genome contains at least 214 variant gene sequences and genetic markers associated with physical performance and health-related fitness phenotypes (Macarthur and North, 2005). Wajchenberg et al (2013) evaluated polymorphisms in two of these genes, angiotensinconverting enzyme (ACE) and α-actinin-3 (ACTN3), in a family with multiple members suffering from AIS. This family had a higher prevalence of the ACE deletion (D) allele, compared with the insertion (I) allele.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, another alternative for genetic studies is the use of molecular markers, previously selected and with a known location in the human genome such as SNPs or snips, which are “silent” chromosomal regions, easily located, without phenotypic manifestation and that show variability of heterozygous alleles. Authors like Aulisa et al [ 55 ], Quiu et al [ 56 ], Chen et al [ 57 ] and Wajchenberg et al [ 58 ], carried out studies of genetic polymorphisms trying to relate AIS with changes in certain genes.…”
Section: Reviewmentioning
confidence: 99%
“…Adolescent idiopathic scoliosis (AIS) is one of the most frequent spinal diseases, with an incidence ranging from 0.5 to 10% in the world population. 1 The spinal instrumentation and fusion procedure for AIS correction is performed frequently in pediatric orthopedic patients. Nevertheless, only 10% of AIS patients require surgical correction.…”
Section: Introductionmentioning
confidence: 99%
“…A escoliose idiopática do adolescente (EIA) é uma das doenças mais frequentes da coluna vertebral, com relatos de uma incidência entre 0,5 e 10% da população mundial. 1 O procedimento de instrumentação espinhal e fusão utilizado para correção de EIA é uma das cirurgias mais frequentemente realizadas em pacientes ortopédicos pediátricos, embora apenas 10% dos portadores dessa doença necessitem de correção cirúrgica. 2 …”
Section: Introductionunclassified